2014
DOI: 10.1093/cvr/cvu163
|View full text |Cite
|
Sign up to set email alerts
|

Delayed phospholamban phosphorylation in post-conditioned heart favours Ca2+ normalization and contributes to protection

Abstract: PoCo reduces SERCA activity at the onset of reperfusion by delaying PLB phosphorylation through activation of PKG and inhibition of PKA and CaMKII. This effect contributes to PoCo protection by favouring cytosolic Ca(2+) extrusion through NCX, and it may be mimicked by pharmacological stimulation of sGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…In the patch-clamp experiments, BAY41-2272 could influence both the whole-cell K + currents and BK Ca currents, and the effect of BAY41-2272 on SMCs in the HS group was weaker than that in the NS. In the presence of KT5823, a specific PKG inhibitor [31], the effect of BAY41-2272 on the K + currents was blocked in both groups. This suggested that the activation of K + currents via sGC needed participation of PKG.…”
Section: Discussionmentioning
confidence: 93%
“…In the patch-clamp experiments, BAY41-2272 could influence both the whole-cell K + currents and BK Ca currents, and the effect of BAY41-2272 on SMCs in the HS group was weaker than that in the NS. In the presence of KT5823, a specific PKG inhibitor [31], the effect of BAY41-2272 on the K + currents was blocked in both groups. This suggested that the activation of K + currents via sGC needed participation of PKG.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, our study suggests that cGMP/PKG‐dependent activation of PDE2 is responsible for the inhibition of PKA while the reduced activity of CaMKII could be the result of PoCo‐dependent attenuation of Ca 2+ overload and ROS production during the first minutes of reperfusion (Erickson et al ., ). The resulting blockade of SERCA activity during the first minutes of reperfusion attenuated the development of hypercontracture and cell death by preventing Ca 2+ oscillations and allowed for Ca 2+ normalization through the Na + /Ca 2+ exchanger and for the activation of endogenous protective signalling pathways that ensure long‐term cardioprotection (Inserte et al ., ).…”
Section: Cgmp/pkg Pathway As a Mediator Of Endogenous Cardioprotectionmentioning
confidence: 97%
“…398 The sarcoplasmic reticulum is a target of PKCε 185 and of protein nitrosylation, 399 POC delays phosphorylation of phospholamban by PKG, and reduced sarcoplasmic reticulum ATPase activity in the presence of acidosis favors the extrusion of cytosolic calcium through the sodium-calcium exchanger and reduces calcium oscillations, thus contributing to reduced IS. 400 Cytoskeleton, Cell Volume, and Ionic Balance Decreased cytoskeletal stability and increased cell volume contribute to membrane disruption and cellular fragility. IPC attenuates osmotic fragility through cytochalasin D-sensitive stabilization of the actin cytoskeleton and a K ATP -dependent mechanism in isolated rabbit cardiomyocytes.…”
Section: Heusch Signal Transduction Of Conditioning 683mentioning
confidence: 99%